(untitled) (Academia Science Repository, 2023)
The aim of this article is to ascertain the connections between secondary school students’ perceptions of language learning courses’ critical thinking tendencies and their support for their own autonomy. A lot of research on this subject, and the results showed a significant relationship between autonomy support and critical thinking tendency. Autonomy support was found to significantly predict critical thinking tendency skills in secondary school students taking language learning classes.